HUBUNGAN PENERAPAN ASI ESKLUSIF, PENGETAHUAN DAN PERAN TENAGA KESEHATAN TERHADAP PENERAPAN METODE AMENOREA LAKTASI DI PUSKESMAS TELANG JAYA TELANG - Thoyibah Azzahra; Amlah Amlah; Eka Afrika (Universitas Pahlawan, 2022)
Lactational Amenorrhea is a contraceptive that relies on exclusive breastfeeding. The Lactational Amenorrhea Method. is a natural family planning method that has a fairly high level of effectiveness, which is 98% if used correctly. The application of the lactational amenorrhea (MAL) method in Indonesia is still low, this is measured by the low level of achievement of exclusive breastfeeding. In general, more people use hormonal contraception. Experts also concluded that women who do not use contraception but breastfeed exclusively or almost exclusively and experience amenorrhoea have less than 2% chance of pregnancy in the first 6 months of postpartum. The purpose of this study was to determine the relationship between the application of exclusive breastfeeding, mother's knowledge and the role of health workers simultaneously on Lactational Amenorrhea in the Telang Jaya Telang Health Center Work Area in 2021. The research design used in this quantitative study was an analytical survey with a cross sectional approach. The research was conducted at the Telang Jaya Telang Health Center with a total of 79 respondents. The results of the chi-square statistical test for the exclusive breastfeeding variable obtained value = (Ï <0.000), knowledge variable obtained value = (Ï <0.001), the role factor of health workers was obtained value = (Ï <0.010) smaller than = 0.05 indicating there is a significant relationship between exclusive breastfeeding , knowledge and role of health workers with lactational amenorrhea in the Telang Jaya Telang Health Center Work Area in 2021. Â KeywordsÂ Â Â Â Â : Exclusive Breastfeeding, Lactational Amenorrhea Method, Knowledge, Role of Health Workers